Gaze Interaction With Vibrotactile Feedback: Review and Design Guidelines. (2nd January 2020) - Rantala, Jussi; Majaranta, Päivi; Kangas, Jari; Isokoski, Poika; Akkil, Deepak; Špakov, Oleg; Raisamo, Roope
Abstract : Vibrotactile feedback is widely used in mobile devices because it provides a discreet and private feedback channel. Gaze-based interaction, on the other hand, is useful in various applications due to its unique capability to convey the focus of interest. Gaze input is naturally available as people typically look at things they operate, but feedback from eye movements is primarily visual. Gaze interaction and the use of vibrotactile feedback have been two parallel fields of human–computer interaction research with a limited connection. Our aim was to build this connection by studying the temporal and spatial mechanisms of supporting gaze input with vibrotactile feedback. The results of a series of experiments showed that the temporal distance between a gaze event and vibrotactile feedback should be less than 250 ms to ensure that the input and output are perceived as connected. The effectiveness of vibrotactile feedback was largely independent of the spatial body location of vibrotactile actuators. In comparison to other modalities, vibrotactile feedback performed equally to auditory and visual feedback. Vibrotactile feedback can be especially beneficial when other modalities are unavailable or difficult to perceive. Based on the findings, we present design guidelines for supporting gaze interaction with vibrotactile feedback.